In‐Plane Directional MoS2 Emitter Employing Dielectric Nanowire Cavity - Alexey Kuznetsov; Maria A. Anikina; Adilet N. Toksumakov; Artem N. Abramov; Vyacheslav V. Dremov; Eseniya Zavyalova; Valeriy M. Kondratev; Vladimir V. Fedorov; Ivan S. Mukhin; Vasily Kravtsov; Kostya S. Novoselov; Aleksey V. Arsenin; et al. (Small Structures)
Two‐dimensional transition metal dichalcogenides (TMDC) exhibit exceptional optical properties, such as strong light‐matter interaction and robust light emission. Nonetheless, their integration into conventional silicon‐based nanophotonic devices, which allow high emission efficiency is still challenging. Herein, a hybrid nanophotonic structure based on monolayer MoS2 and GaP nanowire for the enhancement of the emission and its directional outcoupling through the nanowire is presented. Furthermore, the resonant optical action of the nanowire, which leads to spectral modulation of the MoS2 photoluminescence with a remarkable Q factor exceeding 350 is investigated. The work showcases the achievement of directional in‐plane outcoupling of the 2D TMDC's photoluminescence and its remote optical excitation. These results pave the way to the development of nanoscale laser sources and on‐chip light routing for basic nanophotonic circuitry based on 2D materials.